2020
DOI: 10.3390/polym12091999
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Capsules with Hydrophobic Liquid Cores as Functional Nanocarriers

Abstract: Recent developments in the fabrication of core-shell polymer nanocapsules, as well as their current and future applications, are reported here. Special attention is paid to the newly introduced surfactant-free fabrication method of aqueous dispersions of nanocapsules with hydrophobic liquid cores stabilized by amphiphilic copolymers. Various approaches to the efficient stabilization of such vehicles, tailoring their cores and shells for the fabrication of multifunctional, navigable nanocarriers and/or nanoreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 207 publications
(232 reference statements)
1
18
0
Order By: Relevance
“…Our previous works demonstrated that HyC12-based nanocapsules with liquid hydrophobic cores represent a promising and tunable nanodelivery system for lipophilic active compounds via both, oral and intravenous, administration in vivo. 28 , 29 Interestingly, our in vitro studies revealed that nanocapsules were taken up by mouse liver sinusoidal endothelial cells and lung vascular endothelial cells, suggesting their possible application as a hydrophobic drug delivery system targeted to the vascular wall. 28 Moreover, we showed also the potential for the delivery of lipophilic compounds due to their high stability and efficient uptake by various cells, especially the ones exposing CD44 receptors.…”
Section: Introductionmentioning
confidence: 86%
“…Our previous works demonstrated that HyC12-based nanocapsules with liquid hydrophobic cores represent a promising and tunable nanodelivery system for lipophilic active compounds via both, oral and intravenous, administration in vivo. 28 , 29 Interestingly, our in vitro studies revealed that nanocapsules were taken up by mouse liver sinusoidal endothelial cells and lung vascular endothelial cells, suggesting their possible application as a hydrophobic drug delivery system targeted to the vascular wall. 28 Moreover, we showed also the potential for the delivery of lipophilic compounds due to their high stability and efficient uptake by various cells, especially the ones exposing CD44 receptors.…”
Section: Introductionmentioning
confidence: 86%
“…The latest approach is the use of nanocapsules to deliver RIPs to virus-infected cells. Nanocapsules are vesicular objects in which the encapsulated compound is confined in an internal cavity surrounded by an outer membrane [ 182 , 183 ]. Nanocapsules containing MAP30 [ 180 ] or ricin A-chain [ 181 ] have shown antiviral activity in vitro against HIV.…”
Section: Experimental Therapymentioning
confidence: 99%
“…Most studies focused on the molecular effects of these compounds report dissolving DADS [13,14] and DATS [15] in dimethyl sulfoxide (DMSO). However, during the last few decades, there have been an increasing number of works considering the delivery of hydrophobic actives using drug-delivery systems (DDSs) based on, e.g., polymers, including e.g., polysaccharides [16][17][18][19][20], liposomes [21], bilosomes [22]. In particular, the nanoscale systems are of high interest for the encapsulation of hydrophobic pharmaceuticals and nutraceuticals [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…To address these challenges, the study presented herein includes the encapsulation of sparingly water soluble natural garlic oil compounds (DADS and DATS) aiming mainly at effectively carrying them in physiological environments and protection against oxidation for safe storage and therapeutic action. The formulation is based on nanocapsules with a hyaluronate shell surrounding liquid oil cores dispersed in an aqueous medium [19,37,38]. The hydrophobically modified natural polysaccharide, the sodium salt of hyaluronic acid (HA), constitutes a shell that stabilizes the nanodroplets by the polymeric hydrophobic chains anchoring in the oil core.…”
Section: Introductionmentioning
confidence: 99%